Pre-emptive analgesic effect of lornoxicam in mandibular third molar surgery: a prospective, randomized, double-blind clinical trial. Issue 5 (May 2017) - Mojsa, I.M.; Stypulkowska, J.; Novak, P.; Lipczynski, K.; Szczeklik, K.; Zaleska, M.
Abstract: The aim of this study was to establish whether the pre-emptive use of lornoxicam (16 mg) in third molar surgery ensures successful postoperative analgesia and reduces rescue analgesic intake when compared to postoperative application, and in comparison with placebo. Ninety patients were split randomly into three groups: group A received lornoxicam 60 min before surgery and placebo 60 min after surgery; group B received placebo 60 min before surgery and lornoxicam 60 min after surgery; group C received placebo 60 min before surgery and placebo 60 min after surgery. Postoperative pain was recorded on a visual analogue scale and on a numerical rating scale at 1, 2, 4, 6, 8, 12, and 24 h after surgery. The patients recorded total dose of paracetamol intake during the 24 h after the procedure. The efficacy of postoperative analgesia was greater in lornoxicam groups when compared to the placebo group; there was no difference between the two lornoxicam groups (A and B). Patients in group C took their first rescue analgesic dose earlier after surgery than patients in the two lornoxicam groups. The average dose of paracetamol taken in group C was 1000 mg, while it was 500 mg in the lornoxicam groups.